Soybean Germplasms Performance to Soil Salinity - Abdullah Taufiq; Novita Nugrahaeni; Nuning Agro Subekti; Hasil Sembiring (Balai Penelitian Tanaman Aneka Kacang dan Umbi, 2022)
Saline soil is a prospective land for expanding the soybean planting area in Indonesia, but no variety with the ability to adapt to this soil has currently been released. That objective of this esearch was to identify the salt-tolerant soybean germplasm accessions. The experiment consisted of two treatments and these were arranged in a randomized complete block design with three replications. The first factor was three soil salinity levels i.e. 1.44-1.72 dS/m (used as a check), 6.75±0.40 dS/m, and 10.48±0.30 dS/m. The second factor was 25 soybean accessions selected from previous salinity screening activity. Parameters observed were soil electrical conductivity (EC), plant height, yield and yield attributes, as well as K, Ca, and Na concentration in soil and plant. The results showed that salinity treatment increased the soil EC, Na concentrations in shoot and root, and reduced K, thereby causing a reduction in soybean growth, seed weight, and seed size. Meanwhile, MLGG 0169, MLGG 0640, MLGG 0767 (Lokon variety), MLGG 1109 (Dega 1 variety), and MLGG 1098 (Detam 2 variety) were identified as tolerant tosalinity level up to 10.48±0.30 dS/m. The tolerant genotypes were characterized by high ITC index, high seed yield, fewer reduction of seed yield, and mild leaf damage. The tolerances were likely determined by the ability to absorb more K and less Na, translocate more K from root to shoot, and higher K/Na ratio in shoot and root than Ca/Na ratio. It means the K/Na ratio is more important in determining salinity tolerance than Ca/Na ratio. Therefore, accessions can be used as gene source for salt-tolerant breeding, and Lokon, Dega 1, and Detam 2 varieties were recommended for saline soil.